Mapping Technology, Impact, and Challenges in Nahwu Learning: A Systematic Review (2020–2025) - Hanifa, Zahra Aulia; Sopian, Asep (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This systematic literature review examines technological innovations in Nahwu learning in Indonesia from 2020 to 2025, focusing on three dimensions: types of technology used, educational impact, and implementation challenges. Using the PRISMA framework, 20 peer-reviewed articles were selected based on clear inclusion and exclusion criteria. The findings reveal that Android-based mobile applications, educational games, web platforms, and AI-powered tools are most commonly used, with recent trends favoring adaptive and interactive solutions. These technologies have enhanced student motivation, understanding, and learning flexibility. However, significant challenges persist, including limited infrastructure, low digital literacy among teachers and students, and the need for media tailored to Nahwu’s unique characteristics. Unlike previous reviews, this study holistically synthesizes innovations, impacts, and contextual obstacles, highlighting a research gap in technology integration specific to Nahwu instruction. Limitations include the relatively small number of eligible studies and the potential for publication bias. The review recommends developing context-appropriate learning media, strengthening teacher training, and improving infrastructure to maximize the transformative potential of technology in Nahwu learning. Comprehensive and adaptive strategies are essential to ensure effective and equitable technology integration, supporting the evolving needs of students and educators in the digital era.